2015
DOI: 10.1159/000374049
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Skin Wound Healing in Mammals: State-of-the-Art on Growth Factor and Stem Cell Based Treatments

Abstract: Mammal skin has a crucial function in several life-preserving processes such as hydration, protection against chemicals and pathogens, initialization of vitamin D synthesis, excretion and heat regulation. Severe damage of the skin may therefore be life-threatening. Skin wound repair is a multiphased, yet well-orchestrated process including the interaction of various cell types, growth factors and cytokines aiming at closure of the skin and preferably resulting in tissue repair. Regardless various therapeutic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
112
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(125 citation statements)
references
References 183 publications
1
112
0
6
Order By: Relevance
“…The PDGF-BB dimer -the mostly investigated isoform -is the only one that can bind to all three different surface PDGF receptors (PDGFRs) and trigger different signalling cascades, thus being called the universal isoform of PDGF. Compared to other growth factors, PDGF-BB has a well-established safety profile, approved by the Food and Drug Administration (FDA) (Borena et al, 2015), and formulations supporting wound healing in foot ulcers, as well as, bone regeneration are on the market [Regranex Gel ® (Smith&Nephew, London, UK) and GEM 21S ® (Luitpold, Pharmaceuticals, Shirley, NY, USA)] (Howard et al, 2014;Ma et al, 2015). In chronic foot ulcers, topical application of rhPDGF led to a significant increase (by 43 %) in the incidence of complete wound closure and decrease in healing time (by 32 %) over placebo-controlled wound care, resulting in the FDA approval of Regranex Gel ® (Wieman et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The PDGF-BB dimer -the mostly investigated isoform -is the only one that can bind to all three different surface PDGF receptors (PDGFRs) and trigger different signalling cascades, thus being called the universal isoform of PDGF. Compared to other growth factors, PDGF-BB has a well-established safety profile, approved by the Food and Drug Administration (FDA) (Borena et al, 2015), and formulations supporting wound healing in foot ulcers, as well as, bone regeneration are on the market [Regranex Gel ® (Smith&Nephew, London, UK) and GEM 21S ® (Luitpold, Pharmaceuticals, Shirley, NY, USA)] (Howard et al, 2014;Ma et al, 2015). In chronic foot ulcers, topical application of rhPDGF led to a significant increase (by 43 %) in the incidence of complete wound closure and decrease in healing time (by 32 %) over placebo-controlled wound care, resulting in the FDA approval of Regranex Gel ® (Wieman et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Normal cutaneous wound healing is a complicated process involving three overlapping phases, namely the inflammatory, proliferative, and remodeling phases [1][2][3]. Each phase requires coordinated effects of various cell types, including keratinocytes [4,5], fibroblasts [6], immune cells [7], etc., the disturbance of which in any phase leads to delayed cutaneous wound healing [8].…”
Section: Introductionmentioning
confidence: 99%
“…The development of steroid tapes and plasters has significantly improved the effect of steroid injections when used in combination [7,8]. Besides, stem cell based treatment such as mesenchymal stem cells, hematopoietic stem cells, and skin-derived precursors in wound healing is progressively being valued, but more protracted studies are needed to determine whether the observed effects are clinically significant [9][10][11]. Despite the availability of many therapeutic options, an optimal treatment modality has not been identified to date, underscoring the need to improve our understanding of the mechanisms of keloid formation.…”
Section: Introductionmentioning
confidence: 99%